Senescence mirrors the extent of liver fibrosis in chronic hepatitis C virus infection. Issue 3 (4th June 2018) - Wandrer, F.; Han, B.; Liebig, S.; Schlue, J.; Manns, M. P.; Schulze‐Osthoff, K.; Bantel, H.
Summary: Background: Chronic viral hepatitis is linked to fibrotic liver injury that can progress to liver cirrhosis with its associated complications. Recent evidence suggests a role of senescence in liver fibrosis, although the senescence regulators contributing to fibrosis progression remain unclear. Aim: To investigate the role of senescence and different senescence markers for fibrosis progression in patients with chronic hepatitis C virus (HCV) infection. Methods: The expression of the cell cycle inhibitors p21, p27 and p16 as well as the senescence markers p‐HP1γ and γ‐H2AX was analysed in liver tissue with different fibrosis stages. Senescence‐associated chitotriosidase activity was measured in sera of HCV patients (n = 61) and age‐matched healthy individuals (n = 22). Results: We found a remarkable up‐regulation of the cell cycle inhibitors and senescence markers in chronic HCV infection compared to healthy liver tissue. Liver tissue with relevant fibrosis stages (F2‐3) or cirrhosis (F4) revealed a significant increase in senescent cells compared to livers with no or minimal fibrosis (F0‐1). In cirrhotic livers, a significantly higher number of p‐HP1γ, p21 and p27 positive cells was detected compared to liver tissue with F2‐3 fibrosis. Importantly, we identified T‐cells as the dominant cell type contributing to increased senescence during fibrosis progression. Compared to healthy individuals, serum chitotriosidase was significantly elevated and correlated with histological fibrosis stages and liver stiffness as assessed by transient elastography. Conclusions: Senescence of hepatic T‐cells is enhanced in chronic viral hepatitis and increases with fibrosis progression. Serological detection of senescence‐associated chitotriosidase might allow for the non‐invasive detection of relevant fibrosis stages.